The market behavior as a route of change in the mechanical workshops of Tijuana Baja California - Valladares-Icedo, Omar; Izquierdo-De Dios, Román (EFIM Ediciones, 2020)
Market behavior is one of the most analyzed factors by marketers. This document began with empirical research, based on fndings in the literature and observation, analyzing changes in behavior, in men and women at the time of acquiring a service, especially the mechanical workshop, in the city of Tijuana Baja California. The fndings showed that the company dedicates its eﬀorts to serving the male gender, but that 30% of women serve their automotive service needs, make decisions much more quickly, and enjoy shopping much more. There is a smaller percentage who turn to a male ally for mechanical services, leaving the ally free to make the purchase decision. In contrast, the men who make up 70% of those who purchase this service, argue the workshop solutions, and make the purchase decision with greater difculty. The marketing used in the generic workshop complies empirically with parameters of little measurement, and staﬀ training to improve customer service is a constant to be improved.